Developing a Community-Based Marketing Communication Model to Promote Creative Tourism in Chiang Mai - Bhrammanachote , Winayaporn; Thammo, Thammakit (International Journal of Multidisciplinary in Management and Tourism, 2026)
This study examined the development of a participatory marketing communication model to enhance creative tourism grounded in cultural wisdom in Ban Thung Sieo community, San Pa Tong District, Chiang Mai Province. The research aimed to (1) assess the community’s potential in terms of social capital and existing marketing communication channels, (2) engage the community through participatory action research in developing marketing communication competencies and co-producing promotional media, and (3) develop strategic guidelines for marketing communication reflecting the community’s Lanna cultural identity and supporting sustainable creative tourism growth. A qualitative participatory action research design was employed. Twenty-four key informants comprising community leaders, cultural custodians, local entrepreneurs, and tourism volunteers were selected through purposive sampling. Data was collected during 2024-2025 from in-depth interviews, participant observation, and focus group discussions, then analyzed through qualitative content analysis and triangulation. The findings revealed that while Ban Thung Sieo possesses strong cultural capital rooted in Tai Khoen identity, all existing promotional channels were outdated, spatially inaccurate, and devoid of interactive digital engagement. Across co-design workshops, three practical competencies were developed among community members alongside two tangible outputs including informational infographics and an online digital flipbook. Three strategic guidelines were established addressing digital storytelling, physical infrastructure readiness, and multi-stakeholder governance partnerships. This study contributes a replicable, community-centered participatory marketing communication model offering both practical and theoretical value for sustainable creative tourism development in Chiang Mai and upper northern Thailand.